Strategi Pemasaran Analisis SWOT untuk Meningkatkan PNBP melalui Iklan pada TVRI Sumatera Utara - Dena Pelitawati Maha; Firman Ario (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify marketing strategies to increase Non-Tax State Revenue (PNBP) through advertising on TVRI North Sumatra. This study adopts a qualitative descriptive method involving five respondents as study subjects. The collected data were analyzed using the SWOT approach to identify strategic factors that examine environmental elements both from within and outside the organization identified in the realm of capabilities, deficiencies, opportunities, and challenges faced by TVRI North Sumatra. The research data shows that in the internal context, the strengths of TVRI North Sumatra are slightly greater than its weaknesses, with an IFAS score of 6.076923077 and a positive difference of 0.076923077. Meanwhile, from the external side, threats are more dominant than opportunities, with an EFAS score of 5.946153846 and a negative difference of -0.25. Based on the results of the SWOT analysis, TVRI North Sumatra's position is in Quadrant II, which indicates that despite facing various obstacles, this institution still has internal strength. Internal strengths should be used optimally to explore long-term opportunities with a product diversification strategy.